2020
DOI: 10.2147/dmso.s228674
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low-Magnitude High-Frequency Vibration Decreases Body Weight Gain and Increases Muscle Strength by Enhancing the p38 and AMPK Pathways in db/db Mice</p>

Abstract: Objective: To evaluate the effect LMHFV on body weight gain, NAFLD and muscle strength and explore effect in mitochondrial biogenesis, AMPKα and p38 pathways. Methods: Vibration platform used in this study provides specific whole-body cyclic mechanical stimulation at low magnitude (0.3 g) and high frequency (50 Hz). Diabetic mice (8-9 mice per group) (C57BL/KsJ-m+/+Lepr db) were randomly divided into untreated group (no vibration) and two vibration groups. Lean mice (8 mice) were used as non-diabetic control f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…By inducing diabetes in rats by STZ, the diabetic rats showed significantly elevated blood glucose levels and weight loss as the typical manifestations of type I diabetes mellitus [ 33 ]. With LMHFV treatment, significantly reduced blood glucose was observed, which was consistent with the results reported from previous research in STZ-diabetic rats and db/db mice [ 34 , 35 ]. However, previous studies suggested that LMHFV did not exert any weight gain effect on STZ-diabetic rabbits [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…By inducing diabetes in rats by STZ, the diabetic rats showed significantly elevated blood glucose levels and weight loss as the typical manifestations of type I diabetes mellitus [ 33 ]. With LMHFV treatment, significantly reduced blood glucose was observed, which was consistent with the results reported from previous research in STZ-diabetic rats and db/db mice [ 34 , 35 ]. However, previous studies suggested that LMHFV did not exert any weight gain effect on STZ-diabetic rabbits [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mice underwent 8 rounds of training per day, 3 times of climbing the ladder per round, 1 min rest between each round, lasting 5 days per week for 4 weeks. Vibration exercise refers to the research of Ren et al [ 19 ]. Vibration platform provided vertical vibrations at 50 Hz with a peak-to-peak magnitude of 0.3 g, lasting 15 min per day, 5 days per week for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Vibration may also enhance mitochondrial biogenesis, which normally occurs as a major adaptation of skeletal muscles in response to exercise training. One study found that vibration at 50 Hz enhanced the expression of PGC-1α in the soleus muscle, gastrocnemius muscle and liver, and was associated with increased muscle strength [ 162 ]. PGC1α plays an important role in mitochondrial biogenesis and is regulated by mitogen-activated protein kinase p38 (p38 MAPK) and is activated during exercise.…”
Section: Musculoskeletal Effectsmentioning
confidence: 99%
“…Gloeckl et al [ 161 ] and Lage et al [ 162 ] were able to safely and successfully use vibration therapy as a pulmonary rehabilitation tool for patients with chronic obstructive pulmonary disease (COPD) who require physical exercise but cannot perform due to breathing limitations and general malaise. Although physical exercise is the basis of pulmonary rehabilitation for people with COPD, intense exercise may also stimulates pro-inflammatory cytokines and can be harmful in that context [ 165 , 166 ].…”
Section: Musculoskeletal Effectsmentioning
confidence: 99%